HIV test and knowledge of U=U: insights from MSM living in Portugal and participating in EMIS 2017. (30th September 2020) - Costa, J P; Meireles, P; Aguiar, A; Schmidt, A J; Barros, H
Abstract: Recently, it became clear that undetectable equals untransmittable (U=U), stressing the importance of engaging in medical care and adhering to antiretroviral therapy. HIV testing and counselling (HTC) are offered in different settings and can be an opportunity to inform people. We aimed to understand if HIV testing history, including recency, place and, result, was associated with U=U knowledge. We used data from 2242 MSM living in Portugal participating in EMIS 2017 that answered if they already knew that "A person with HIV who is on effective treatment (called 'undetectable viral load') cannot pass their virus to someone else during sex", opting of 5 possible answers, dichotomized in "I already knew" vs. any other option. Regarding HIV testing history, participants were categorized as follows:1. HIV positive; 2. HIV negative and last test ≤12 months in a community setting; 3. HIV negative and last test ≤12 months in a medical setting, and 4. never tested for HIV or last test >12 months or tested in other settings (reference). Logistic regression models were fitted to estimate crude and city size and education-adjusted associations. The median (P25; P75) age of participants was 34 (25; 43) years. No significant statistical association was found with age or current occupation. Those with more years of education and living in a big or very big city were more likely to know that U=U (aOR:1.55; 95%CI:1.20-1.99 and aOR:1.26; 95%CI:1.04-1.53, respectively). Considering HIV testing history and diagnosis, men with diagnosed HIV (aOR:6.33; 95%CI:4.50-8.90), those who had the last test in community setting (aOR:2.44; 95%CI:1.87-3.17) and those who had the last test in a medical setting (aOR: 1.57; 95%CI:1.26-1.95) were more aware of U=U than those not tested in the last 12 months. Our results suggest that there is a gradient of U=U knowledge associated with HIV testing history among MSM. Efforts should focus on improving counselling about U=U at all HIV testing settings. Key messages: The knowledge of U=U seems to be associated with the place, recency and result of the last HIV test. Counselling should focus on the best evidence available at all HIV testing settings, to inform and empower the individuals.